Analysis of the Need for Nahwu Teaching Materials for Qur’an Memorizers - Ruhmadi, Abdul; Farisi, Mohamad Zaka Al; Zulfikhar, Akbar Fatih (UIN Mahmud Yunus Batusangkar, Indonesia, 2024)
This study aims to assess the need for nahwu (Arabic grammar) teaching materials for Quran memorization students. A deep and accurate understanding of the Quranic verses requires mastery of nahwu. However, many Quran memorization students face challenges in learning nahwu due to the teaching materials not aligning with their needs. This research uses a descriptive qualitative method with a needs analysis approach. The analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The research participants consisted of the Vice Principal of Curriculum Affairs and 27 students at PTQ Maqdis. The main activity of PTQ Maqdis students is memorizing and reviewing their Quranic memorization. Data was collected through structured interviews with the Vice Principal of Curriculum Affairs at PTQ and by having 27 PTQ students complete a needs analysis questionnaire. The results of the interviews showed that PTQ Maqdis uses Matan al-Ajurrumiyah in nahwu learning and that there is a need for nahwu teaching materials with a discovery model grounded in Quranic verses. Meanwhile, the students’ questionnaire revealed that 78.2% of the students, or the majority, need teaching materials with a discovery-based model grounded in Quranic verses. Based on these findings, there is a need for the development of the Matan al-Ajurrumiyah book with a discovery model grounded in Quranic verses.